Analisis Gender Wage Gap pada Sektor Formal dan Informal di Indonesia: Studi Data Sakernas 2023 - Rahma, Nazelia; Kirana, Mayanggita (Jurnal Dinamika Ekonomi Pembangunan, 2025)
The gender wage gap remains a persistent issue in Indonesia despite regulations promoting gender equality. This study analyzes wage disparities between men and women in formal and informal sectors using data from the 2023 National Labor Force Survey (Sakernas). A quantitative approach is employed, applying Ordinary Least Squares (OLS) on ln(wage) and Recentered Influence Function-OLS (RIF-OLS) to examine the gap across wage distribution quintiles. The results show that there is a wage gap between men and women with a significant negative effect, the penalty to women is greater in the informal sector with a coefficient of -0.4180 (significant at 1%) than the formal sector with a coefficient of -0.3415 (significant at 1%). In addition, the RIF-OLS results show that the wage gap is uneven across the income distribution, the sticky floor phenomenon is identified in the formal sector, indicated by the highest wage penalty against women in the lower quintile. This reflects that women are more disadvantaged at low wage levels and face barriers to upward mobility. In contrast, there is no strong indication of a glass ceiling, as the wage penalty in the upper quintile is smaller than in the lower and middle levels in both the formal and informal sectors.